2012
DOI: 10.1099/vir.0.034876-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural modelling and mutagenesis of human cytomegalovirus alkaline nuclease UL98

Abstract: Human cytomegalovirus encodes an alkaline nuclease, UL98, that is highly conserved among herpesviruses and has both endonuclease (endo) and exonuclease (exo) activities. This protein is thought to be important for viral replication and therefore represents a potential target for antiviral development; however, little is known about its structure or role in viral replication. Comparative structural modelling was used to build a model of UL98 based on the known structure of shutoff and exonuclease protein from K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Both mutations abolish the ability of UL12 to complement the growth defect of a UL12-null mutant virus (29). Mutagenesis of EBV, HCMV, and KSHV UL12 orthologs has also demonstrated that residues analogous to UL12 G336, S338, and D340 are critical for nuclease activity (30,(32)(33)(34). We included three additional mutations that have also been shown to eliminate detectable nuclease activity in vitro and abolish complementing activity in vivo; ⌬N, L150K, and ⌬C (23).…”
Section: Resultsmentioning
confidence: 99%
“…Both mutations abolish the ability of UL12 to complement the growth defect of a UL12-null mutant virus (29). Mutagenesis of EBV, HCMV, and KSHV UL12 orthologs has also demonstrated that residues analogous to UL12 G336, S338, and D340 are critical for nuclease activity (30,(32)(33)(34). We included three additional mutations that have also been shown to eliminate detectable nuclease activity in vitro and abolish complementing activity in vivo; ⌬N, L150K, and ⌬C (23).…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant UL98 was inducibly expressed in Escherichia coli BL21 (DE3) lys S and purified using methods modified from those previously described ( Kuchta et al, 2012 ). The UL98 expression vector pD17–98(wt) ( Kuchta et al, 2012 ) was modified to contain an N-terminal sequence encoding two tandem histidine (his 6 ) tags.…”
Section: Methodsmentioning
confidence: 99%
“…Impaired replication has been linked to defects in DNA processing, capsid stability, and capsid nuclear egress ( Martinez et al, 1996 , Porter and Stow, 2004 , Shao et al, 1993 , Weller et al, 1990 ). Recently our group showed that a CMV UL98 null mutant is severely compromised for replication ( Kuchta et al, 2012 ). At least one function of the CMV UL98 is likely to be similar to HSV-1 UL12 since the CMV UL98 gene can functionally complement the replication defect of HSV-1 UL12 null viruses ( Gao et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…3C). Proximity of the T172P mutation to the reported 5=-phosphate-binding pocket and catalytic active site in other viral nucleases likely prevents proper substrate binding, cleavage, and release, possibly due to proline-dependent protein misfolding (21,22).To further characterize VZV ORF48 protein nuclease activity, 500 ng undigested (circular) pCI-Neo DNA was examined for endonuclease activity. Undigested plasmid DNA consisted of both nicked (relaxed circular, RC) and supercoiled (SC) DNA (Fig.…”
mentioning
confidence: 99%
“…3C). Proximity of the T172P mutation to the reported 5=-phosphate-binding pocket and catalytic active site in other viral nucleases likely prevents proper substrate binding, cleavage, and release, possibly due to proline-dependent protein misfolding (21,22).…”
mentioning
confidence: 99%